PRODUCTION OF FRESH VEGETABLE ROOT CROPS OF THE FAMALY BRASSICACEAE IN OPEN FIELD AT VARIOUS TIME OF GROWING - Y. K. Zemskova; A. V. Savchenko (Овощи России)
The data of spring-summer sowing time of vegetable root crops of the family Brassicaceae in the open filed are presented. Five varieties and three hybrids of daikon, seven varieties of radish, and four varieties of turnip were tested. Based on the results, the minimal and maximal root weight for each time of sowing were determined; average fresh weight of vegetable roots for three years of investigation was accounted.